Some effects of topographic aspect on grassland responses to elevated CO2. (3rd July 2019) - Lieffering, Mark; Newton, Paul C. D.; Brock, Shona C.; Theobald, Phillip W.
ABSTRACT: Grasslands are distributed globally across various topographies. In non-flat grasslands, aspect (the direction that a slope faces) influences the amounts of radiation and consequent effects on temperature and soil moisture, all of which are important drivers of plant growth. Aspect is important not only in hill and mountain areas but also in more moderate topographies such as plateaux, steppes and prairies. Here, we tested the aboveground growth response to an important driver of climate change – elevated carbon dioxide (eCO2 ) – of two temperate grass species grown under simulated north (unshaded) and south (shaded) aspects. We used trellis-like structures to create the appropriate radiation regimes; irrigation ensured that only radiation and hence soil temperatures were different. We utilised the long-running New Zealand Free-Air Carbon Dioxide Enrichment (FACE) experiment and established turves of Lolium perenne L. and Agrostis capillaris L. The aboveground dry matter (DM) was regularly harvested over 10 months. For the main effects, there was no overall response to CO2 but Agrostis produced about 50% more DM than Lolium while the north aspect produced about 15% more DM than the south. There was an interaction between CO2 level and aspect: for both species production was about 20% greater under eCO2 on the north aspect but had no effect on the south aspect. Given that a large proportion of the world's grasslands is on slopes, this aspect × CO2 interaction causes us to reconsider the up-scaling of CO2 responses from FACE experiments that have been universally carried out on flat terrain.